2m+6n+7m+9n=

Simple and best practice solution for 2m+6n+7m+9n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+6n+7m+9n= equation:


Simplifying
2m + 6n + 7m + 9n = 0

Reorder the terms:
2m + 7m + 6n + 9n = 0

Combine like terms: 2m + 7m = 9m
9m + 6n + 9n = 0

Combine like terms: 6n + 9n = 15n
9m + 15n = 0

Solving
9m + 15n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-15n' to each side of the equation.
9m + 15n + -15n = 0 + -15n

Combine like terms: 15n + -15n = 0
9m + 0 = 0 + -15n
9m = 0 + -15n
Remove the zero:
9m = -15n

Divide each side by '9'.
m = -1.666666667n

Simplifying
m = -1.666666667n

See similar equations:

| 3x+y=.14 | | 3x+6-2x=32 | | 20-14x=48 | | 3x+6+-2x=32 | | (8x)2=84 | | 0.40x+0.90(400)=0.50(400+x) | | 10x^2+5xy=0 | | 3x+6-2x=30 | | .25x+1.6=.5x-4.5 | | 12Cx+1=12Cx+5 | | 253+36n=469 | | 8N(2n-5)=4n+8 | | u^2+u-1=-9 | | 4x+6y=-15 | | 2+3x-2=24 | | -7(7-6)=-70 | | 19=-3(24-m)+2(m-2) | | 7y-5=4x+12 | | (3x^2+7x)(2x-5)=0 | | iz+3=-1+2i | | 14+6x=x+1 | | X-2.3=4.7 | | 4.9t^2+78.4=0 | | -[4x-(2x+4)]=-5-[3(2x-4)-2x] | | 4(3z+1)-8=56 | | 12m+9m-8c+c+15= | | 5y+7y=35 | | 10x^2-53x+63=0 | | 9a+10(6aq-1)= | | X-4=-5.6 | | -2x^3+3x^2-x-36=48 | | -2x^3+3x^2-x-36=38 |

Equations solver categories